Tropical cyclones of the North Atlantic Ocean, 1871-1992 - Elms, Joe D; Neumann, Charles J; United States. National Environmental Satellite, Data, and Information Service; United States. National Weather Service; National Hurricane Center (U.S.); National Climatic Data Center (U.S.) (Asheville, N.C. : National Climatic Data Center, 1993)
Mode of access: Internet.